Direct observation of atomically-resolved silver species on a silver alumina catalyst active for selective catalytic reduction of nitrogen oxides. Issue 22 (3rd October 2019) - Kannisto, Hannes; Skoglundh, Magnus; Arve, Kalle; Olsson, Eva; Härelind, Hanna
Abstract : We characterize the size and state of the silver species in a 2 wt% silver alumina catalyst, which is highly active for the selective catalytic reduction of nitrogen oxides with ammonia or hydrocarbons as reductant. Abstract : We characterize the size and state of the silver species in a 2 wt% silver alumina catalyst, which is highly active for the selective catalytic reduction of nitrogen oxides with ammonia or hydrocarbons as reductant. The silver alumina catalyst is prepared by a single-step sol–gel method and characterized with X-ray photoelectron and ultraviolet-visible spectroscopy, and high-resolution transmission electron microscopy. We show, for the first time, direct observations of atomically-resolved silver species and silver clusters on the silver alumina catalyst. The results determine the existence of these silver species on the alumina support, which corroborate previously reported indirect observations, and strengthen the hypothesis of small silver clusters as active sites for the selective catalytic reduction of nitrogen oxides.